Preliminary Characterization of Phytochemicals and Polysaccharides in Diverse Coffee Cascara Samples: Identification, Quantification and Discovery of Novel Compounds - Jiarong Zhang; Xuequan Sun; Pinhe Liu; Tongze Zhang; Joel A. Jelderks; Harold Corke (Foods, 2022)
Coffee cascara is the first and most significant by-product of the coffee processing industry, whose valorization has become an urgent priority to reduce harmful environmental impacts. This work aimed to provide an improved understanding of phytochemicals and polysaccharides in coffee cascara in order to offer information for the better evaluation of potential applications. Phytochemicals in 20 different coffee cascara samples were ultrasonically extracted and analyzed by HPLC-UV and HPLC-MS/MS. Four novel compounds were isolated for the first time from coffee cascara, including two still unknown tautomers (337 Da), and two dihydroflavonol glycosides (dihydromyricetin glycoside and dihydromyricetin rhamnosylglycoside). Their presence can contribute to the design of new value-added applications of coffee cascara. Chemical characterization of two polysaccharides from two of the coffee cascara pulp samples showed that they were mainly composed of homogalacturonan, with rhamnose and arabinose as minor neutral sugars. In addition, principal component analysis results indicated that coffee cultivar and/or country significantly impacted the phytochemical composition of coffee cascara, although differences may be reduced by the external environment and processing method. It is suggested that processing method should be carefully designed when generating coffee cascara from the same cultivar and country/farm.